2012
DOI: 10.1016/j.jinsphys.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Physalin B inhibits Trypanosoma cruzi infection in the gut of Rhodnius prolixus by affecting the immune system and microbiota

Abstract: Physalin B is a natural secosteroidal, extracted from the Solanaceae plant, Physalis angulata, and it presents immune-modulator effects on the bloodsucking bug, Rhodnius prolixus. In this work, R. prolixus was treated with physalin B at a concentration of 1 mg/ml of blood meal (oral application), or 20 ng/insect (applied topically) or 57 ng/cm(2) of filter paper (contact treatment), and infected with Trypanosoma cruzi Dm28c clone (2×10(6) epimastigotes/insect). The three types of applications significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This could be a result of TFM excretion or detoxification. It has been shown that gut microbes have an important role in the detoxification of ingested xenobiotics [63], and it has been described that, after a blood meal, there is a huge increase in the bacterial population in R. prolixus gut contents [64, 65]. However, our data suggest that oral treatment does not affect diuresis (Figures 1 and 2), so the elimination of TFM in urine after oral treatment should also be considered.…”
Section: Discussionmentioning
confidence: 61%
“…This could be a result of TFM excretion or detoxification. It has been shown that gut microbes have an important role in the detoxification of ingested xenobiotics [63], and it has been described that, after a blood meal, there is a huge increase in the bacterial population in R. prolixus gut contents [64, 65]. However, our data suggest that oral treatment does not affect diuresis (Figures 1 and 2), so the elimination of TFM in urine after oral treatment should also be considered.…”
Section: Discussionmentioning
confidence: 61%
“…Since withanolides possess antibacterial properties1926, they potentially affect the composition of larval gut microbiota. For example, in Rhodnius prolixus, a blood-sucking bug and an important vector of the Chagas disease, withanolide treatment resulted in higher numbers of bacterial microbiota but also in a lower antibacterial activity45. The fact that we found an increase in the relative weight gain in H. subflexa larvae feeding on diet containing withanolides suggests that withanolides have a nutritional or digestive microbial-driven effect, which reached its full potential at a concentration of 100 μg of withanolides in our experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Castro and co-workers corroborated these findings, showing that physalin B inhibits T. cruzi development in the gut of triatomines (Castro et al . 2009, 2012). However, the anti- T. cruzi activity of physalins against the infective forms in humans (bloodstream trypomastigotes and amastigotes) have not been described.…”
Section: Discussionmentioning
confidence: 99%
“…2008; Castro et al . 2009, 2012). The findings suggest physalins are useful compounds for vector-borne transmission control.…”
Section: Introductionmentioning
confidence: 99%